Ukraine's Revolt, Russia's Revenge : Revolution, Invasion, and a United States Embassy - Smith, Christopher M. (Diplomat) (Book collections on Project MUSE., 2022)
"Told from the perspective of a U.S. diplomat in Kyiv, this book is the true story of Ukraine's anti-corruption revolution in 2013-14, Russia's intervention and invasion, and the limited role played by the United States. The author's narrative includes a wealth of information on Ukrainian high-level and street-level politics, a broad analysis of the international context, and vivid descriptions of people and places in Ukraine during the EuroMaidan Revolution. The book also counters Russia's disinformation narratives about the revolution and America's role in it. While focusing on a single country during a dramatic three-year period, the book's universal themes-among them, truth versus lies, democracy versus autocracy-possess a broader urgency for our times, particularly for the United States and all other countries that are the targets of Russia's cyber warfare and other forms of political skullduggery. The book also details Russia's attempt to abort the Ukrainian revolution through threats, economic pressure, lies, and intimidation. When all of that failed, the Kremlin exacted revenge by annexing Ukraine's territory of Crimea and fomenting and sustaining a hybrid war in eastern Ukraine that has killed more than 13,000 people and continues to this day"--